Impaired cognitive function and decreased monoamine neurotransmitters in the DNAJC12 gene knockout mouse model - Shunan Wang; Ming Shen; Bo Pang; Bo Zhou; Yuan Yuan; Mei Lu; Xiangling Deng; Min Yang; Shufang Liu; Qiong Wang; Mei Xue; Qisheng Xia; et al. (Orphanet Journal of Rare Diseases)
Abstract Background Hyperphenylalaninemia, a prevalent amino acid metabolism disorder, often results in cognitive impairment. Recent studies have identified a rare variant of this disorder caused by mutations in the DNAJC12 gene. The specific mechanisms by which DNAJC12 mutations lead to hyperphenylalaninemia and the lack of an animal model for study remain significant gaps in understanding. Purpose This study aims to elucidate the role of DNAJC12 in intellectual disability and explore the mechanisms by which DNAJC12 deficiency leads to hyperphenylalaninemia through developing a DNAJC12 gene knockout mouse model. Methods We thoroughly examined the clinical features and genetic mutations evident in two patients with biallelic mutations in the DNAJC12 gene. Based on the patient’s mutation locations, we determined the target site for the knockout utilizing CRISPR/Cas9 technology. To assess the impact of these mutations on DNAJC12 expression, we used quantitative real-time PCR and Western blotting techniques to measure mRNA and protein levels, respectively. The Morris water maze test was administered to evaluate the cognitive functions of the mice. Additionally, we utilized High-Performance Liquid Chromatography (HPLC) to measure serum aromatic amino acids and brain monoamines, facilitating an investigation into the metabolism of phenylalanine and tyrosine. Results We reported two patients with mutations in the DNAJC12 gene. Case 1 carried the mutations c.158-1G > A and c.262 C > T in the DNAJC12 gene. He presented with nocturnal eye closure, crying, and arching back in reverse tension before treatment, suggesting a neurotransmitter metabolism disorder. Case 2 carried the mutations c.473 C > G, and c.102 deletion in the DNAJC12 gene. He showed elevated blood phenylalanine levels, although further clinical details were not available. Based on the patients’ mutation locations, exons 2–4 of the DNAJC12 gene were targeted and eliminated. In our animal model experiments, DNAJC12 gene knockout mice exhibited a complete absence of DNAJC12 expression at both mRNA and protein levels. These knockout mice showed significant deficits in learning and memory performance as assessed by the Morris water maze test. Quantitative real-time PCR analysis indicated no significant differences in the levels of aromatic amino hydroxylases between knockout and wild-type mice. However, Western blot analysis revealed a substantial reduction in phenylalanine hydroxylase (PAH) protein levels in the liver of knockout mice, while tyrosine hydroxylase (TH) and tryptophan hydroxylase 2 (TPH2) expression remained unchanged. HPLC analysis demonstrated increased serum Phe concentrations and decreased levels of brain neurotransmitters in the knockout group. Conclusions We report two patients with four novel DNAJC12 mutations (c.158-1G > A, c.262 C > T, c.473 C > G, c.102delT), expanding the mutation spectrum. Based on the patients’ mutation location, we established the first DNAJC12 gene knockout mouse model. The knockout mice exhibit hyperphenylalaninemia, impaired cognitive function, and decreased monoamine neurotransmitters. DNAJC12 deficiency may contribute to the clinical phenotype via the PAH pathway, potentially at the post-transcriptional level.